Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1088/0741-3335/58/1/014032
|View full text |Cite
|
Sign up to set email alerts
|

Globus-M plasma physics research for fusion application and compact neutron source development

Abstract: During the past decade, plasma physics research promoting the physics base of ITER and developing novel concepts such as a compact fusion neutron source has been conducted on the Globus-M spherical tokamak (ST) (R = 36 cm, a = 24 cm, I p ⩽ 250 kA, B T ⩽ 0.4 T). Tokamak reconstruction is imminent. The upgraded tokamak Globus-M2 will have the same vacuum chamber and an enhanced magnetic system to provide B T = 1 T and I p = 500 kA. In this paper we outline the most important research directions and the main resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 27 publications
(32 reference statements)
2
13
0
1
Order By: Relevance
“…GAMs were identified in the spherical tokamak Globus-M [6,7] was discovered as coherent oscillations of perpendicular velocity in 20-35 kHz frequency range provided the backscatter region was located inside the separatrix [8][9][10]. This frequency range was in line with theoretical estimations performed for the conditions of the Globus-M periphery [11].…”
Section: Geodesic Acoustic Modesupporting
confidence: 84%
“…GAMs were identified in the spherical tokamak Globus-M [6,7] was discovered as coherent oscillations of perpendicular velocity in 20-35 kHz frequency range provided the backscatter region was located inside the separatrix [8][9][10]. This frequency range was in line with theoretical estimations performed for the conditions of the Globus-M periphery [11].…”
Section: Geodesic Acoustic Modesupporting
confidence: 84%
“…Transport quantities and turbulence parameters were provided by the ELMFIRE gyrokinetic code. The modeling results have shown satisfactory agreement with the experiments: (1) in TUMAN-3M the GAM parameters threshold for L-H transition is determined (figure 4), however for FT-2 the transition was not possible for experimental GAM parameter sets [18]; (2) in the case of the pellet injection, L-H transition occurred if a part of the pellet was disintegrated in the pelletguide, resulting in a gas/'snow' puff so that the pellet ablation is peripheral; on the contrary, if the pellet is evaporated deeper in the plasma, there is no L-H transition [19].…”
Section: L-h Transitionsupporting
confidence: 70%
“…DBS was implemented to study geodesic acoustic modes (GAMs) on the Globus-M tokamak in the Ohmic phase of discharges at relatively low plasma density (n ≈ (2-3) × 10 19 m −3 ) when the toroidal ion drift was directed away from the X-point [35][36][37]. All DBS systems (see Table 1) and in some experiments even their combinations were used to obtain information about various properties of GAMs presented in Table 3 (see the end of Section 3.1).…”
Section: Geodesic Acoustic Modementioning
confidence: 99%
“…It was shown that an SMBI pulse can reduce the Doppler shift frequency, which corresponds to the flattening of the electric field. In a series of experiments on the EAST tokamak using two separate DBS systems, one for the Q-band (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) and the other for the V-band (50-75 GHz), Doppler shifted signals were obtained and radial profiles of perpendicular velocities were computed for the L-and H-mode [15]. In the Globus-M2 tokamak, the first results of the Doppler backscattering diagnostics during a discharge with the L-H transition show that the transition process is linked to the deformation of the poloidal rotation velocity profile [16].…”
Section: Introductionmentioning
confidence: 99%